Long‐term outcome of 154 patients receiving balloon‐occluded retrograde transvenous obliteration for gastric fundal varices. Issue 11 (November 2016) - Imai, Yukinori; Nakazawa, Manabu; Ando, Satsuki; Sugawara, Kayoko; Mochida, Satoshi
Abstract: Background and Aim: This study aims to clarify the long‐term outcome of therapeutic strategies including balloon‐occluded retrograde transvenous obliteration (B‐RTO) for patients with gastric fundal varices. Methods: The subjects were 154 patients with gastric fundal varices fulfilling the criteria for receiving B‐RTO. In patients showing variceal bleeding, endoscopic therapies and/or balloon tamponade was performed to achieve hemostasis. B‐RTO was accomplished with injection of 5% ethanolamine oleate through a standard balloon catheter except for patients with atypical varices, in whom a microballoon catheter was used to occlude drainage vessels other than a gastrorenal shunt. In patients complicated with esophageal varices at baseline, endoscopic therapies were performed following B‐RTO. Results: Balloon‐occluded retrograde transvenous obliteration was performed successfully in 147 patients (95%), including 15 patients using a microballoon catheter. Complete variceal obliteration was achieved in all patients. Additional endoscopic therapies for esophageal varices were performed in 31 patients. Gastric varices did not recur in any of these patients. The cumulative survival rates at 1, 3, and 5 years after B‐RTO were 91%, 76%, and 72%, respectively. Child‐Pugh scores and hepatocellular carcinoma complication were identified as prognostic factors associated with survival rates. The cumulative exacerbation rates of esophageal varices at 1, 3, and 5 years were 13%, 20%, and 27%, respectively, and rupture developed in six patients, which were successfully treated with endoscopic therapies. Conclusions: Therapeutic strategies including B‐RTO with a microballoon catheter were useful to achieve a favorable outcome in patients with gastric fundal varices especially in those manifesting Child‐Pugh class‐A liver damage and/or those without hepatocellular carcinoma complication.